Using mobile laser scanner and imagery for urban management applications - Gonzalez-Barbosa, Jose-Joel; Flores-Rodrıguez, Karen Lizbeth; Ornelas-Rodrıguez, Francisco Javier; Trujillo-Romero, Felipe; Gonzalez-Barbosa, Erick Alejandro; Hurtado-Ramos, Juan B. (Institute of Advanced Engineering and Science, 2022)
Despite autonomous navigation is one of the most proliferate applications of three-dimensional (3D) point clouds and imagery both techniques can potentially have many other applications. This work explores urban digitization tools applied to 3D geometry to perform urban tasks. We focus exclusively on compiling scientific research that merges mobile laser scanning (MLS) and imagery from vision systems. The major contribution of this review is to show the evolution of MLS combined with imagery in urban applications. We review systems used by public and private organizations to handle urban tasks such as historic preservation, roadside assistance, road infrastructure inventory, and public space study. The work pinpoints the potential and accuracy of data acquisition systems to handled both 3D point clouds and imagery data. We highlight potential future work regarding the detection of urban environment elements and to solve urban problems. This article concludes by discussing the major constraints and struggles of current systems that use MLS combined with imagery to perform urban tasks and to solve urban tasks.